2001
DOI: 10.1046/j.1464-410x.2001.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physiotherapy for female urinary incontinence: individual compared with group treatment

Abstract: Objectives To compare, in a randomized trial, the effects of individual and group physiotherapy for urinary incontinence in women referred by their general practitioner (GP). Patients and methods The study included women of all ages (mean 47.8 years) with stress, urge or mixed incontinence; 126 received individual and 404 group treatment. Both groups undertook the same pelvic oor exercises and bladder training, and received the same information. The effects were measured soon after treatment and again 9 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 11 publications
1
42
3
2
Order By: Relevance
“…19,20 Some studies concluded that providing physical therapy for urinary incontinence in a group format results in clinical results equivalent to the same treatment in the individual format. 6,7,21,22 Also, evidence shows that PFMT in a group format has clinical outcomes equivalent to an individual format in the treatment of stress urinary incontinence. 8,23,24 A systematic review comparing the effectiveness of PFMT in group versus individual PFMT versus PFMT performed at home for the conservative treatment of female urinary incontinence, found through meta-analysis that there was no difference when comparing PFMT in group versus individual PFMT.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Some studies concluded that providing physical therapy for urinary incontinence in a group format results in clinical results equivalent to the same treatment in the individual format. 6,7,21,22 Also, evidence shows that PFMT in a group format has clinical outcomes equivalent to an individual format in the treatment of stress urinary incontinence. 8,23,24 A systematic review comparing the effectiveness of PFMT in group versus individual PFMT versus PFMT performed at home for the conservative treatment of female urinary incontinence, found through meta-analysis that there was no difference when comparing PFMT in group versus individual PFMT.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the model shows a relationship between less frequent use of the task-oriented style and a higher level of HRQOL. It may seem that this dependence should be rather the reverse, since, in the opinion of many researchers (Janssen et al, 2001) coping with the symptoms of urinary incontinence requires a task-oriented approach.…”
Section: Discussionmentioning
confidence: 99%
“…on the road from work to home), using single-use sanitary pads and napkins, and keeping a log of urination (Kinn & Zaar, 1998;Fitzerald et al, 2001;Janssen et al, 2001). These techniques correspond, interestingly enough, with both a task-oriented approach and an avoidance approach (all forms of restriction, such as avoiding fluids), though this is seldom stated directly.…”
Section: Discussionmentioning
confidence: 99%
“…With the individual training, the length of each session and the time of treatment are smaller. However, in the group treatment there is the reinforcement of motivation among the participants 20 (LE 3; DR B). Oliveira Camargo et al 21 compared these two treatment techniques in women with stress UI and observed that, after 12 weeks, both groups obtained significant reductions of UI and improved QOL, without significant differences 21 (LE 1; DR A).…”
Section: (Le 1; Dr A)mentioning
confidence: 99%